La evitación social y las relaciones interpersonales de las y los adolescentes del Segundo Año de Bachillerato Paralelos K y L del Colegio Fiscomisional Daniel Álvarez Burneo de la ciudad de Loja. Periodo 2014 - 2015 - Sarango Jaramillo, Maricela Paola (2015)
This thesis research aims to determine the influence social avoidance in relationships of the adolescents; identify social avoidance cases by age and gender; investigate the types of relationships; clarify the causes of social avoidance and finally develop a plan of psychoeducation aimed at improving the social avoidance and strengthen relationships. Inductive-deductive and analytical-synthetic method was used, including techniques and instruments used to achieve the objectives outlined in the research are: the Social Phobia Inventory aimed at identifying cases of social avoidance by age and gender and structured surveys aimed to investigate the types of relationships and also identify the causes of social avoidance. The universe was formed about 480 students in the second year of high school, taking a significant sample of 70 adolescents, a representation of 30% of the total population. According to the results of the occurrence of social avoidance it was demonstrated with a higher prevalence in females, aged between 16 and 18; also a high rate of dependent relationships are determined, also it was identified among the causes of social avoidance, as major affective relationship of the parents; among the most prevalent features are; overprotective, demanding, domineering or authoritarian, little or no emotional parents. Another fundamental cause was also established in relation to humiliating and traumatic events experienced during childhood. (Teasing, contempt, ridicule, rejection, criticism, etc.) KEYWORDS. Social avoidance, Relationships, adolescents.